Discrete and looking (to profit): homoconnectivity on Grindr. - Aunspach, Chase (Critical Studies in Media Communication, 2020)
The queer dating and hookup app Grindr evidences a technological and economic intensification in queer spaces online. The dominant modality of capitalist power is no longer consumerist norms but the collection and analysis of data. Grindr's participation in datafication distributes increased risks upon its queer users and necessitates a renewed politics of queer privacy beyond homonormativity. I name this arrangement of power homoconnectivity and detail four techniques that capitalism deploys to capture and monetize queer social production. Ultimately, this article unpacks how Grindr designs experiences that move users to log into the app while hiding its engagement with multi-sided markets. Oscillating between producing continuous experiences and deploying annoying constraints, platforms like Grindr privatize and monetize user spaces, communities, social production, and lives under the guise of increased connectivity. With the goal of building more just queer worlds, homoconnectivity makes legible new pressure points to push back against the growing ubiquity of capitalist datafication and queer world-taking.